The Elusive Search for Teacher Collaboration. Issue 1 (2nd January 2017) - Glazier, Jocelyn A.; Boyd, Ashley; Bell Hughes, Kristen; Able, Harriet; Mallous, Ritsa
ABSTRACT: Collaboration is a well-used term in the field of education, identified as promising practice for student learning and teaching learning alike. However, collaboration comes in different shapes and sizes, leading to radically different ends. The authors examine teachers' own understandings and practices of collaboration with teacher colleagues within their school contexts and within a professional development model designed to allow for collaborative conversation between teachers. Implications for teacher education are then considered.